2001
DOI: 10.1046/j.1365-2044.2001.01789.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of midazolam pretreatment on induction dose requirements of propofol in combination with fentanyl in younger and older adults

Abstract: SummaryIn a double-blind, randomised trial, we compared the effects of pretreatment with midazolam at two different doses (0.025 and 0.05 mg.kg 21 ), with placebo, on the induction dose requirements of propofol in two different age groups. We enrolled 120 patients: 60 younger patients (aged 18± 35 years) and 60 older patients (aged over 60 years). All patients received 0.75 m g.kg 21 of fentanyl, plus a blinded pretreatment with either saline or one of two doses of midazolam. Induction continued with a fixed r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
47
1
4

Year Published

2010
2010
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 20 publications
3
47
1
4
Order By: Relevance
“…There was 45.37% reduction in the induction dose of propofol with midazolam co-induction. Earlier studies[1415] also support the reduction in the induction dose of propofol after midazolam pre-treatment.…”
Section: Discussionmentioning
confidence: 79%
“…There was 45.37% reduction in the induction dose of propofol with midazolam co-induction. Earlier studies[1415] also support the reduction in the induction dose of propofol after midazolam pre-treatment.…”
Section: Discussionmentioning
confidence: 79%
“…Under these studies, the hypnotic sparing effect of midazolam probably allowed higher rates of excellent intubating conditions to be reached with a lower dose of remifentanil. [16][17][18] Second, assessment of intubating conditions was performed using a different scale from that used in the studies by Durmus et al 9 and Mohammadreza and Azim. 10 In fact, we used the standardized qualitative scoring system proposed by the consensus conference on GCRP in Pharmacodynamic Studies of Neuromuscular Blocking Agents in 1996 for the assessment of the intubating conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Khajabi et al the ketofol has shown to have an effec ve seda ve property and is be er than other combina on of 16 propofol with fentany and pethidine. In addi on, the ketofol combina on has low incidence of psychomime c 10,11 reac on of ketamine seen in the postopera ve room. These two molecules can be successfully mixed in a single syringe propofol are physically compa ble for 1 hr at 23⁰ C. In another study done by RF Donnelly the combina on of ketamine and propofol in either 50:50 or 30:70 propor on in a plas c syringe were physically and chemically stable for at least 3 hr when stored at room temperature with 18 exposure of light.…”
Section: Discussionmentioning
confidence: 99%